Internationalization of SME’s in India - A comparative study between the Manufacturing and Service sectors - Viswanatha Reddy, Chandu (2014)
Internationalization of Indian SMEs has been increasing in the past few years; this paper studies the internationalization process of the Indian software and manufacturing SMEs and has compared and contrasted salient features between them. 8 SMEs, 4 from each sector were studied in order to gain insights in the field of SME internationalization in a developing nation such as India. Key theories such as born global, network, resource and knowledge based theories are discussed and employed in this study. The importance of effectuation theory is highlighted by this empirical study and suggests further research in this field. The findings are supported by the existent literature which coherently conveys that no single theory can truly explain the internationalization of SMEs.